2013
DOI: 10.3390/ijms14035998
|View full text |Cite
|
Sign up to set email alerts
|

Alteration of Podocyte Protein Expression and Localization in the Early Stage of Various Hemodynamic Conditions

Abstract: Given that podocalyxin (PCX) and nestin play important roles in podocyte morphogenesis and the maintenance of structural integrity, we examined whether the expression and localization of these two podocyte proteins were influenced in the early stage of various hemodynamic conditions. Mice kidney tissues were prepared by in vivo cryotechnique (IVCT). The distribution of glomeruli and podocyte proteins was visualized with DAB staining, confocal laser scanning microscopy and immunoelectron microscopy. The mRNA le… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
7
0

Year Published

2014
2014
2019
2019

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 9 publications
(7 citation statements)
references
References 28 publications
(31 reference statements)
0
7
0
Order By: Relevance
“…Podocalyxin, located on the surface of podocytes that faces the urinary space, is one of the major negatively charged glomerular proteins in the glomerular basement membrane and plays an important role in the maintenance of the intricate glomerular basement membrane and plays an important role in the maintenance of the intricate glomerular podocyte for optimal filtration [ 22 ]. The increased urinary PCX (Upcx) excretion is a particularly sensitive index for indicating podocyte injury in patients with diabetes and can be used as an early specific indicator of glomerular podocyte dysfunction [ 23 , 24 ]. In fact, decreased mRNA expression and protein components of slit diaphragm are related to the degree of proteinuria in several models of kidney diseases [ 25 ].…”
Section: Discussionmentioning
confidence: 99%
“…Podocalyxin, located on the surface of podocytes that faces the urinary space, is one of the major negatively charged glomerular proteins in the glomerular basement membrane and plays an important role in the maintenance of the intricate glomerular basement membrane and plays an important role in the maintenance of the intricate glomerular podocyte for optimal filtration [ 22 ]. The increased urinary PCX (Upcx) excretion is a particularly sensitive index for indicating podocyte injury in patients with diabetes and can be used as an early specific indicator of glomerular podocyte dysfunction [ 23 , 24 ]. In fact, decreased mRNA expression and protein components of slit diaphragm are related to the degree of proteinuria in several models of kidney diseases [ 25 ].…”
Section: Discussionmentioning
confidence: 99%
“…As a key protein of podocytes, podocalyxin plays an important role in renal injury in hypertension. Kai et al 11 demonstrated that under normal conditions, PCX stains more intensely along glomerular epithelial cells, whereas with acute hypertension, PCX staining is unclear with a disarranged distribution. They also reported that the mRNA levels were significantly decreased.…”
Section: Discussionmentioning
confidence: 99%
“…65 Injury of these cells leads to cascade of changes in the molecular architecture of the slit diaphragm due to reorganization of the foot processes. 34,35,64 In this study, podocytes of the three nephrectomized rat groups showed disrupted minor processes, irregular nuclei, prominent mitochondria and numerous lysosomes, with disruption of Bowman's basement membrane and widening of …”
mentioning
confidence: 99%
“…59 The podocytes gain a special importance as they line the basement membrane of the glomerulus, which, therefore, forms the final filtration barrier against proteinuria. 64 They are the key regulator of the basement membrane in both physiologic and pathologic conditions. 65 Injury of these cells leads to cascade of changes in the molecular architecture of the slit diaphragm due to reorganization of the foot processes.…”
mentioning
confidence: 99%